2012
DOI: 10.3109/08820139.2012.695417
|View full text |Cite
|
Sign up to set email alerts
|

PGE2-Driven Induction and Maintenance of Cancer-Associated Myeloid-Derived Suppressor Cells

Abstract: Myeloid-derived suppressor cells (MDSCs) are critical mediators of tumor-associated immune suppression, with their numbers and activity strongly increased in most human cancers and animal models. MDSCs suppress anti-tumor immunity through multiple mechanisms, including the manipulation of arginine and tryptophan metabolism by such factors as arginase (Arg), inducible nitric oxide synthase (iNOS/NOS2), and indoleamine-2,3-dioxygenase (IDO). Prostaglandin E(2) (PGE(2)), a mediator of chronic inflammation and tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
90
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(93 citation statements)
references
References 148 publications
3
90
0
Order By: Relevance
“…Studies of MDSCs in cancer identified a variety of factors inducing and activating MDSC function (25,(38)(39)(40). We could now show that the human trophoblast cell line JEG-3 induced MDSCs with high suppressive activity.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Studies of MDSCs in cancer identified a variety of factors inducing and activating MDSC function (25,(38)(39)(40). We could now show that the human trophoblast cell line JEG-3 induced MDSCs with high suppressive activity.…”
Section: Discussionmentioning
confidence: 53%
“…JEG-3-induced MDSCs expressed increased levels of CXCR4 similar to freshly isolated plaGRMDSCs, and pharmacologic blockade of CXCR4 resulted in reduced inhibitory capacity. CXCR4 has been previously implicated in migration and activation of MDSCs in cancer (40,41). CXCL12, the ligand for CXCR4, has been shown to be expressed by trophoblast and decidual stromal cells and to be responsible for homing of decidual NK cells (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…Prostaglandin E 2 (PGE 2 ) directly suppresses various immune cells such as macrophages, neutrophils, Th1, CTL and NK cells, while it promotes Th2, Th17 and regulatory T cell responses as well as the development of tumor-associated suppressive macrophages [93,[100][101][102][103]. The Th17-promoting activity of PGE 2 is related to its ability to suppress the production of the Th17-inhibitory IL-12, while enhancing the Th17-supporting IL-23 secretion by dendritic cells [104].…”
Section: Pgementioning
confidence: 99%
“…Indeed, PGE 2 has been shown to stimulate IL-23/IL-17-induced neutrophil migration in inflammation by inhibiting IL-12 and IFNγ production, which may be one mechanism for its pro-inflammatory effect [105]. PGE 2 also promotes MDSC recruitment to tumor through the local induction of CXCL12/SDF-1 [100]. In addition, PGE 2 promotes the recruitment of CD4 + CD25 + Tregs to the tumor and has direct positive effects on tumor progression [106].…”
Section: Pgementioning
confidence: 99%
“…Immune suppression: The hallmark of myeloid derived suppressor cells (Haile et al, 2012); PGE(2)-driven induction and maintenance of cancer-associated myeloidderived suppressor cells (Obermajer et al, 2012); Myeloid-derived suppressor cells adhere to physiologic STAT3-vs STAT5-dependent hematopoietic programming, establishing diverse tumor-mediated mechanisms of immunologic escape (Cohen et al, 2012); Myeloid-derived suppressor cells and anti-tumor T cells: A complex relationship (Monu & Frey, 2012); Highlights on molecular mechanisms of MDSCmediated immune suppression: Paving the way for new working hypotheses (Solito et al, 2012); Phenotypic plasticity of MDSC in cancers (Manjili, 2012); Indoleamine 2,3-dioxygenase and dendritic cell tolerogenicity (Harden & Egilmez, 2012); Myeloid-derived suppressor cells (MDSCs) in gliomas and glioma-development (Kohanbash & Okada, 2012); Saccharomyces as a vaccine against systemic Candidiasis (Liu et al, 2012).…”
Section: Il-18mentioning
confidence: 99%